Bangla hate speech detection on social media using attention-based recurrent neural network - Das, Amit Kumar; Al Asif, Abdullah; Paul, Anik; Hossain, Md. Nur (De Gruyter, 2022)
This article was published in the Journal of Intelligent Systems by De Gruyter [© 2021 Amit Kumar Das et al., published by De Gruyter, This work is licensed under the Creative Commons Attribution 4.0 International License.] and the definite version is available at: https://doi.org/10.1515/jisys-2020-0060 The Journal's website is at: https://www.degruyter.com/document/doi/10.1515/jisys-2020-0060/html